A simple mathematical model for the spread of two political parties - Misra, Arvind Kumar Kumar (Nonlinear Analysis: Modelling and Control, 2012)
In this paper, a non-linear mathematical model for the spread of two political parties has been proposed and analyzed by using epidemiological approach. The whole population is assumed to be a constant and homogeneously mixed. Equilibria have been obtained analytically and their local and global stability have been discussed. Conditions for the co-existence of both the political parties have been obtained. Numerical simulation is also performed to support the analytical results.